Pentasulfurated benzene-cored asterisks: relationship between crystal structure and luminescence properties. (6th February 2020) - Villa, Marco; D'Agostino, Simone; Sabatino, Piera; Noel, Raymond; Busto, José; Roy, Myriam; Gingras, Marc; Ceroni, Paola
Abstract : Pentasulfurated benzene chromophores are not luminescent in fluid solution and are phosphorescent in the solid state; in particular, the cyano-derivative which displays a bright orange luminescence. Abstract : Room temperature phosphorescence by metal-free chromophores is quite a rare phenomenon. Hexasulfurated benzene-cored molecules with phenyl substituents, hereafter named asterisks, display bright green phosphorescence in the solid state at room temperature, while they are not luminescent in solution, because of fast non-radiative decay of the lowest excited state. Some of these asterisks are also among the most phosphorescent compounds. Following a search for structure–property relationships, we report here the synthesis, characterization, crystal structure and optical properties of three pentasulfurated benzene-cored asterisks, carrying at the sixth position of the benzene core a cyano (A5CN ), a carboxaldehyde (A5CHO ), or a vinyl group (A5CC ). The most luminescent compound is A5CN, displaying an intense orange phosphorescence in the solid state. Our actual aim is to try and correlate the optical properties with the crystal structure in this series of compounds.